Nawal El-Saadawi: Membongkar Budaya Patriarkhi Melalui Sastra - Kulsum, Ummu (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Abstrak: Nawal el-Saadawi, an Egyptian feminist, which dismantle patriarchal culture in Egypt, through the work of the controversial novel "Woman at Point Zero" a phenomenal work because it makes the Egyptian government blocked all literary works. So el-Saadawi owns exodus to America because his life is not safe in his own country. This novel literary work is a true story of a woman named paradise. Firdaus was sentenced to hanging for killing a pimp - in this novel tells the vagaries of life. From the time of his childhood in the village, until he became a top class prostitute in the city of Cairo. He welcomed the heart punishment. Even he firmly rejected clemency to the president proposed by the prison doctor. According to paradise, it is precisely the verdict is the only path to true righteousness. Ironic. This phenomenal literary work, terms of the patriarchal system that is so powerful in the Egyptian city. Although there are much more works of el-Saadawi, who gave the feel of the uprising of a feminist Nawal el-Saadawi, as plaintiff, he was imprisoned, chased, stalked a herd of armed security guards. A threat to el-Saadawi is still desperate to voice his inner anxiety because they feel unfairly treated. Songs of freedom will not stop, you could have silenced any threat.